Exercise Behaviors and Fatigue in Patients Receiving Immunotherapy for Advanced Melanoma: A Cross-Sectional Survey via Social Media. (July 2019) - Hyatt, Amelia; Drosdowsky, Allison; Williams, Narelle; Paton, Elizabeth; Bennett, Fiona; Andersen, Hayley; Mathai, Jared; Milne, Donna
Objective: Treatment with immunotherapy has positively changed the long-term outlook of many patients with advanced melanoma; however, fatigue is a common and debilitating side effect. Evidence indicates exercise can improve treatment-related fatigue for patients receiving chemotherapy and radiotherapy. However, currently little is known about exercise behaviors and preferences of patients receiving immunotherapy. This project aimed to describe self-reported levels of fatigue related to immunotherapy; patient perspectives of exercise behaviors; and barriers and facilitators to engagement in exercise for patients receiving, or recently completed immunotherapy for unresectable stage III and stage IV melanoma.Method: A cross-sectional purpose-built survey was distributed to members of the Melanoma Patients Australia closed Facebook group via an online survey platform. The survey remained active for 1 month, with 3 posts during this time inviting members to participate.Results: A total of 55 responses were collected. Just over half the participants (n = 31; 56%) described exercising while receiving immunotherapy, with walking as the most common activity (n = 24; 77%). Participants described a range of physical and emotional benefits of exercise, the most predominant being fatigue reduction. Barriers to exercise also included fatigue and competing physical demands at home or work. Patient understanding of what constitutes exercise appeared to differ from clinical classifications.Conclusions: Results from this study indicate that patients are engaging in exercise while receiving immunotherapy, with the intent of mediating treatment-related fatigue. Identification of preferred exercise activities and barriers will assist in developing tailored exercise interventions for this cohort.